A mobile system for whole eye perfusion supporting retinal function and surgery - Lohss, Maxwell; Samski, Katelin S.; Liasis, Alkiviades; Aweidah, Hamzah; Komatsu, Chiaki; Beale, Oliver; Lee, Daniel M. W.; Rossi, Ethan A.; Shroff, Sanjeev G.; Sahel, José A.; Stefko, S. Tonya; Byrne, Leah C. (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionThe use of human donor tissue has the potential to accelerate translational research and support the development of effective human medicines. However, post-mortem sample degradation and the loss of anatomical context limits the utility of primary tissue.MethodsHere, an ex vivo perfusion platform, the Advancing Straight-to-Human Eye Research (ASTHER) system, was designed to perfuse whole eyes with autologous blood to support ex vivo viability. The system was designed for portability and compatibility with modern surgical techniques. ResultsFeasibility trials of ophthalmic artery cannulation, arterial perfusion, retinal imaging, and electroretinography with the ASTHER platform were performed.Discussion Qualitative imaging and electroretinography confirmed post-enucleation retinal blood supply and neuronal function in perfused Yucatan mini pig eyes. Retinal surgery was performed in perfused eyes. A pilot study showed the applicability of the minipig enucleation and perfusion protocol in donated human tissue. Future validation studies of the ASTHER platform will quantify perfused tissue structure and function.